Social deprivation and admission for neonatal care. Issue 4 (21st June 2005) - Manning, D; Brewster, B; Bundred, P
Abstract : Objective: To determine whether social deprivation is associated with neonatal unit admission. Setting: English district general hospital. Method: Retrospective review of neonatal unit admission records between 1990 and 2002. Results: There was a linear increase in admission rates with increasing deprivation. The admission rate was 6.1% of live births for infants in the most affluent quartile compared with 11.1% for those in the most deprived quartile. Admission rates for all indications except jaundice and feeding problems increased with increasing deprivation. Conclusion: Social deprivation correlates strongly with neonatal morbidity and the need for neonatal unit admission. This finding has implications for professionals in public health and primary and secondary care.